Archaeological Excavations at Gudri Historical Mosque in Old City, Kabul - Hamraz, Muzhgan; Najimi, AbdulWasy (Journal of Social Sciences - Kabul University, 2020)
Historical monuments serve as symbols of cultural identity in society. The Gudri Historical Mosque is located in the old city of Kabul. Archaeological evidence indicates that the Mughal King Shah Jahan initially built the mosque, which was later preserved by King Aurangzeb in the 16th century. The mosque suffered damage during the civil war and has undergone multiple conservation efforts. Since 2015, the Aga Khan Trust for Culture (AKTC) has been restoring the mosque as part of an educational program. This initiative has provided valuable training opportunities for students in the fields of architecture, archaeology, and history. The Gudri Mosque is not just a place of worship but also an exceptional training center where students gain hands-on experience. This article aims to explain the archaeological excavation process and the evidence uncovered to highlight the mosque’s role in the educational development of these disciplines.